(untitled) (Theatrum historiae, 2010)
If we look at the relationship between women and money in numismatic terms, in the history of Bohemia we can find several interesting women who minted their own money or were at least involved in the production of money. In the Middle Ages these included Duchess Emma Regina († 1006), the wife of the Bohemian Duke Boleslaus II, and Eufemia of Hungary († 1111), the wife of the Olomouc duke Ota I the Fair. From the Silesian princely family of Legnica-Brzeg we know of several women who acquired the right to mint their own coins upon the death of their husband and with their own sons not having come of age. These are Anna Těšínská (†1367), Anna Maria of Anhalt († 1605) and Ludvika of Anhalt († 1680). In the Těšín family, Princess Elizabeth Lucretia († 1653) was granted the right to mint her own coins in 1638 by Emperor Ferdinand III. Women’s minting came to a majestic peak in Bohemia with Queen Maria Theresa (1740-1780). In the 16th century women also appear in the Bohemian mints (Prague and Jáchy- mov), where after the death of their husband (master of the mint) they took on the running of the mint, at least for a certain amount of time. Even in somewhat unfortunate lines of “business”, such as counterfeiting money, there was generally a woman who acted as a faithful partner for her husband.